2017
DOI: 10.1099/jmm.0.000420
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of partial VP7 gene of the emerging human group A rotavirus G12 strains circulating in Tunisia

Abstract: Thus, the Tunisian G12 strains may have originated from not a single, but at least three distinct ancestral G12 strains. Detailed molecular characterization of the entire genome of these strains remains essential to help determine the extent of genetic variation and the relatedness of Tunisian G12 RVA strains to G12 strains described worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Moreover, G12P [8] and G12P [6] were the most prevalent genotypes being responsible for over 43 % of all rotavirus infections in Ivorian children [38,53]. In the MENA region, G12 was reported in Saudi Arabia (7 %) [10], Yemen (2 %) [11], Iraq (7 %) [12], Iran (9.4 %) [13], Egypt (9.2 %) [16], Tunisia (5.2 %) [14,15], Pakistan (12.85 %) [17,54] and Turkey (15.6 %) [18]. In Lebanon, G12 accounted for 1.6 % of all rotavirus infections [21], where the sole genotype detected was G12P [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, G12P [8] and G12P [6] were the most prevalent genotypes being responsible for over 43 % of all rotavirus infections in Ivorian children [38,53]. In the MENA region, G12 was reported in Saudi Arabia (7 %) [10], Yemen (2 %) [11], Iraq (7 %) [12], Iran (9.4 %) [13], Egypt (9.2 %) [16], Tunisia (5.2 %) [14,15], Pakistan (12.85 %) [17,54] and Turkey (15.6 %) [18]. In Lebanon, G12 accounted for 1.6 % of all rotavirus infections [21], where the sole genotype detected was G12P [6].…”
Section: Discussionmentioning
confidence: 99%
“…They have emerged predominantly in combination with either P [6] or P [8], and less commonly with P [4] or P [9] genotype. In the Middle East and North Africa (MENA), G12 strains have been reported in several countries; Saudi Arabia [10], Yemen [11], Iraq [12], Iran [13], Tunisia [14,15], Egypt [16], Pakistan [17] and Turkey [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on epidemiological data and phylogenetic analysis, G12 strains are subdivided into four lineages (I–IV) 38 . Sequence analysis of VP7 gene showed that all HP G12 RVAs clustered within the modern lineage‐III, indicating the derivation of these strains from a common origin.…”
Section: Discussionmentioning
confidence: 99%
“…G5, G8 and G10 have been identified recently in different parts of the world, including India, Ghana, Australia, Argentina, Paraguay and Malawi (Hoshino, Jones, Ross, & Kapikian, ). Recently, the G12 genotypes have been re‐emerged in humans in the United States (Wylie, Stanley, Tekippe, Mihindukulasuriya, & Storch, ), Spain (Cilla, Montes, & Arana, ) and Tunisia (Moussa et al, ). The remarkable diversity of human RVA strains is associated with three major evolutionary mechanisms: the accumulation of point mutations leading to antigenic drift; reassortment of cognate genome segments promoting antigenic shift; and the reassortment of genes in strains found in animals that could introduce new antigen types into humans (Martella, Bányai, Matthijnssens, Buonavoglia, & Ciarlet, ; Matthijnssens et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…G5, G8 and G10 have been identified recently in different parts of the world, including India, Ghana, Australia, Argentina, Paraguay and Malawi (Hoshino, Jones, Ross, & Kapikian, 2003). Recently, the G12 genotypes have been re-emerged in humans in the United States (Wylie, Stanley, Tekippe, Mihindukulasuriya, & Storch, 2017), Spain (Cilla, Montes, & Arana, 2014) and Tunisia (Moussa et al, 2017).…”
mentioning
confidence: 99%